Effect of cardiac rehabilitation on quality of life in myocardial infarction patients in Zanjan - sadeghzadeh, Vida; Moshtagh eshgh, Zahra (Advances in Nursing & Midwifery, 2012)
Effect of cardiac rehabilitation on quality of life in myocardial infarction patients in Zanjan Sadegh Zadeh V (MSN) 1, Moshtagh Eshgh Z (MSN) 2 1. Lecturer, Dept. Surgical, midwifery Dept, Islamic Azad University, Zanjan Branch, Zanjan, Iran 2. Lecturer, Dept. of Nursing, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran Abstract Background and aim Acute heart diseases cause limitation in physical activity and problems in quality of life. The aim of this study was to determine the effect of cardiac rehabilitation on quality of life in myocardial infarction patients in Zanjan. Materials and methods The current study is a two group and a pre & post test experimental study. 60 patients were selected and randomly assigned in two groups, control group and experimental group. For data collection, demographic questionnaire and Nottingham Health Profile (NHP) were used. Content validity of questionnaire was measured by content validity and reliability by Test-re-Test (r=0.82). Intervention program included, individual training, nutrition and mental counseling and exercise program. From each of the two groups control and experimental pre-test and post-test examinations were taken. Data were analyzed by SPSS v16 and descriptive and analytical statistics (T test, repeated measurement ANOVA) were used. Findings The results show a significant difference in the quality of life scores of the control and experimental groups (P=0.001 Mean=1.55 S.E=0.41, P=0.000 Mean=2/71 S.E=0.59, respectively). Thus, cardiac rehabilitation program is effective on quality of life of MI patients in the experimental group. According to results, the average score of the eight week (experimental: P=0.000 Mean=0/64 S.D=1.42 control: P=0.001 Mean=2.27 S.D=2.20) was better than that of the third week (experimental: P=0.000 Mean=3.35 S.D=2.73 control: P=0.001 Mean= 3.82 S.D=2.13) for both groups. This is more drastic in the experimental group. Furthermore, results showed no significant difference between the quality of life scores of men and women. Conclusion The cardiac rehabilitation program can affect and improve the quality of life. Providing rehabilitation centers, gives the patients the chance to use these programs and gives them a better chance of independence life. Keywords: Cardiac rehabilitation, Myocardial infarction, Quality of life, Exercise. *Corresponding Author: Vida Sadeghzadeh. Department of Nursing, Zanjan Branch, Islamic Azad University, Zanjan, Iran. E-mail: vidasadegh@yahoo.com